Full spectrum cytometry improves the resolution of highly autofluorescent biological samples: Identification of myeloid cells in regenerating skeletal muscles. Issue 10 (24th May 2022) - Kharraz, Yacine; Lukesova, Vera; Serrano, Antonio L.; Davison, Adam; Muñoz‐Cánoves, Pura
Abstract: Autofluorescence (AF) is an intrinsic characteristic of cells caused by the presence of fluorescent biological compounds within the cell; these can include structural proteins (e.g., collagen and elastin), cellular organelles, and metabolites (e.g., aromatic amino acids). In flow cytometric studies, the presence of AF can lead to reduced antigen and population resolution, as well as the presence of artifacts due to false positive events. Here, we describe a methodology that uses the inherent ability of full spectrum cytometry to treat AF as a fluorochrome and to thereby separate it from the other fluorochromes of the assay. This method can be applied to complex inflamed tissues; for instance, in regenerating skeletal muscle we have developed a 16‐color panel targeting highly autofluorescent myeloid cells. This represents a first step toward overcoming technological limitations in flow cytometry due to AF.